Dielectric material preparation from pineapple leaf fiber based on two-level factorial analysis and its morphological structure - Mohamad Shaiful, Abdul Karim; Norazwina, Zainol; N. H., Aziz; N. S., Mat Hussain; Nurhafizah, Abu Talip Yusof (Kuwait University, 2024)
Natural fiber has earned great attention for its discovery as a green material in dielectric composites. Their excellent dielectric properties have granted them the great capability to be used in high dielectric composites. Hence, this study attempts to determine the most influential factor contributing to the permittivity of pineapple leaf fibers and to examine the morphological structure of the developed fibers. The two-level factorial analysis was applied to determine the significant, influential factors and the best conditions contributing to the permittivity value of fiber. The factors include the pineapple leaf-to-soda ratio (1:5 and 1:10), soda concentration (5–10 wt%), temperature (60–100 ℃), and pulping time (45–75 min). The fiber was extracted from the pineapple leaf through the soda pulping method, and the content was analyzed by the Kurschner-Hanack method. Based on the analysis, the pineapple leaf-to-soda ratio was observed as the most significant factor contributing to the permittivity value of fiber, with an 8.86% contribution. The best conditions were suggested at a 1:10 pineapple leaf-to-soda ratio, 5 wt% soda concentration, 100 ℃ temperature, and 45 min of pulping time, contributing to the 1.85 permittivity value of pineapple leaf fiber. The scanning electron microscope images of the material under test indicate that the morphological structures play a crucial part in determining the permittivity value of fiber. Therefore, with suitable processing factors, pineapple leaf fiber can be a great dielectric material used in many engineering applications.